PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 007 KOTO TALUK KECAMATAN KUANTAN TENGAH - Lidia Kartika; Mahmud Alpusari; M. Jaya Adiputra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This background of this research is the low Science learning achievement of the third grade students of SDN 007 Koto Taluk at Kuantan Tengah sub distric, which based on the average score of 16 students, 5 of them passed the standard of minimum completeness of mastery learning (KKM) while 11 of them did not with class’ average score of 59,93. At the same time, the standar of minimum completeness of mastery learning (KKM) is 72. The purpose of this study is to improve the Science learning achievement of the third grade students of SDN 007 Koto Taluk at Kuantan Tengah sub distric through quantum teaching model. The type of this research is action research. The data collection technique used were the students’ science learning achievement and observation sheets. A test was used to find out the students’ science learning achievement whereas observation sheets were used to collect the data on the teachers’ and students’ activities. The science learning achievement pre treatment show a percentage of 31,25%. The learning results post treatment in cycle I shows an improvement of 56,25% in percentage, 87,5% in cycle II and the 93,75% in cycle III. Based on the results, it can be concluded that the implementation of quantum teaching model to improve the science learning achievement on the third grade students of SDN 007 Koto Taluk at Kuantan Tengah sub distric is effective.Key Words : Quantum Teaching Model, science learning achievement